Analisis Pengelolaan Keuangan Dana Desa (Studi Kasus Desa Dampang Kabupaten Bulukumba) - Suci Aulia Salsabilah Usri; Samirah Dunakhir; Samsinar Samsinar (Jurnal Ilmiah Manajemen, Ekonomi dan Akuntansi, 2025)
This study aims to determine the management of village funds in Dampang Village, Bulukumba Regency. The variables in this study are: financial management of village funds consisting of 5 stages, namely planning, implementation, administration, reporting, and accountability of village funds. The population of this research is all village fund management reports and documents that support the village fund management process as well as village officials related to village fund management in Dampang Village, Bulukumba Regency, while the sample is the village fund management report and documents related to village fund management and village officials related to fund management in Dampang Village, Bulukumba Regency in 2023. Data collection techniques were carried out using documentation supported by interviews. Data analysis was carried out with comparative descriptive. The results of this study indicate that the management of village funds in Dampang Village, Bulukumba Regency is only in accordance with the implementation, administration and accountability stages, while the planning and reporting stages are not in accordance with the Regulation of the Minister of Home Affairs Number 20 of 2018 concerning Village Financial Management.